SRPP, a Cell Wall Protein is Involved in Development and Protection of Seeds and Root Hairs in Arabidopsis thaliana. (30th January 2017) - Tanaka, Natsuki; Uno, Hiroshi; Okuda, Shohei; Gunji, Shizuka; Ferjani, Ali; Aoyama, Takashi; Maeshima, Masayoshi
Abstract : Enhancement of root hair development in response to phosphate (Pi) deficit has been reported extensively. Root hairs are involved in major root functions such as the absorption of water, acquisition of nutrients and secretion of organic acids and enzymes. Individual root hair cells maintain these functions and appropriate structure under various physiological conditions. We carried out a study to identify protein(s) which maintain the structure and function of root hairs, and identified a protein (SEED AND ROOT HAIR PROTECTIVE PROTEIN, SRPP) that was induced in root hairs under Pi-deficient conditions. Promoter assay and mRNA quantification revealed that SRPP was expressed in root hairs and seeds. A knockout mutant, srpp-1, consistently displayed defects in root hairs and seeds. Root hairs in srpp-1 were short and the phenotypes observed under Pi-deficient conditions were also detected in ethylene-treated srpp-1 plants. Propidium iodide stained most root hairs of srpp-1 grown under Pi-deficient conditions, suggesting cell death. In addition to root hairs, most srpp-1 seeds were withered and their embryos were dead. SRPP tagged with green fluorescent protein was detected in the cell wall. Electron microscopy showed abnormal morphology of the cell wall. Wild-type phenotypes were restored when the SRPP gene was expressed in srpp-1. These data strongly suggest that SRPP contributes to the construction of robust cell walls, whereby it plays a key role in the development of root hairs and seeds.